A systematic review and meta-analysis of randomized controlled trials of cognitive-behavioral therapy for tinnitus distress - Hesser, Hugo; Weise, Cornelia; Westin, Vendela Zetterqvist; Andersson, Gerhard (Clinical Psychology Review, 2011)
Tinnitus is defined as a sound in the ear(s) and/or head without external origin and is a serious health concern for millions worldwide. The aim of the present study was to determine whether Cognitive Behavior Therapy (CBT) is effective in reducing distress associated with tinnitus. Randomized, controlled trials that assessed the efficacy of CBT for tinnitus-related distress in adults were identified by searching electronic databases (PsychINFO, PubMed, the Cochrane Library), and by manual searches. Fifteen studies (total of 1091 participants) were included in the meta-analysis. CBT compared with a passive and active control at post-assessment yielded statistically significant mean effect sizes for tinnitus-specific measures (Hedges's. g = 0.70, and Hedges's. g = 0.44, respectively). The average weighted pre-to-follow-up effect size for the CBT group suggested that these effects were maintained over time. Smaller but yet statistically significant effects of CBT were found for mood outcome measures. Characteristics of the studies were unrelated to effect sizes. Methodological rigor, publication bias, and a series of sensitivity analyses did not influence the findings. The results suggest that CBT is an effective treatment of tinnitus distress. However, caution is warranted given that few large-scale, well-controlled trials were identified. © 2010 Elsevier Ltd.
CRIS-Team Scopus Importer:2024-03-27
Keywords: Cognitive-behavioral therapy; Efficacy; Meta-analysis; Tinnitus